A CFD approach for local thermal stress assessment inoccupied built environments. (29th August 2007) - Kang, Z. J.; Xue, H.; Bong, T. Y.
A numerical approach is developed for local thermal stress assessment in occupied built environments. A CFD airflow model is coupled with a human thermoregulation model to simulate the basic environmental parameters with having regard to the occupant body heat rejection and moisture emission. Effective temperature (ET) and wet bulb globe temperature (WBGT) are used as the heat indices for indoor thermal stress assessment. Algorithms for computation of three dimensional (3-D) distributions of the heat indices are established, so that local thermal stress levels at certain locations in the environment can be predicted and evaluated according to the simulation results of the basic parameters. A demonstrative analysis for a crowded rectangular space with mechanical ventilation is given.